Fbxl10/Kdm2b Recruits Polycomb Repressive Complex 1 to CpG Islands and Regulates H2A Ubiquitylation - Wu, Xudong; Johansen, Jens Vilstrup; Helin, Kristian (Molecular cell, 2013)
Polycomb repressive complex 1 (PRC1) catalyzes lysine 119 monoubiquitylation on H2A (H2AK119ub1) and regulates pluripotency in embryonic stem cells (ESCs). However, the mechanisms controlling the binding of PRC1 to genomic sites and its catalytic activity are poorly understood. Here, we show that Fbxl10 interacts with Ring1B and Nspc1, forming a noncanonical PRC1 that is required for H2AK119ub1 in mouse ESCs. Genome-wide analyses reveal that Fbxl10 preferentially binds to CpG islands and colocalizes with Ring1B on Polycomb target genes. Notably, Fbxl10 depletion causes a decrease in Ring1B binding to target genes and a major loss of H2AK119ub1. Furthermore, genetic analyses demonstrate that Fbxl10 DNA binding capability and integration into PRC1 are required for H2AK119 ubiquitylation. ESCs lacking Fbxl10, like previously characterized Polycomb mutants, cannot differentiate properly. These results demonstrate that Fbxl10 has a key role in regulating Ring1B recruitment to its target genes and H2AK119 ubiquitylation in ESCs. [Display omitted] ► Fbxl10 binds to most CpG islands in ESCs ► Fbxl10 recruits Nspc1 and Ring1B to CpG islands ► The Fbxl10, Nspc1, and Ring1B complex is required for H2A monoubiquitylation ► Fbxl10 is required for proper ESC differentiation